Herniorrhaphy with anesthesia local empowered - Ribero, Gustavo; Varela Palmer, Daniel; Cimarra Figueiras, Fernando; Acevedo, Carlos; Caraballo, Mónica; Genta, Fernando (Cirugía del Uruguay, 1996)
The authors present the analysis of a prospective series of fifty-two patients who underwent different coordina/ion herniorraphy procedures under potentiated local anesthesia. They present anatomical and pharmacological basis, selection criteria far inclusion and details of anesthesic technique. They point out the feasabi!ity of herniorraphy far any herniary topography; a large variety of repairs were completed with good intra-operative comfort. This anesthesic technique does not increase morbimortality and it is ideal in the organiza/ion of ambulatory surgery programmes.